A situação penal das pessoas físicas nos acordos de leniência com base na Lei nº. 12.846/13 - Mattos, Rodrigo Castor de (2022)
Law n. 12.846/13, known as Anti-Corruption Law, brought, among other provisions, the possibility for companies involved in acts against the public administration to sign leniency agreements with public authorities. The leniency agreement is an important instrument that allows obtaining information and evidence in the context of the investigation of crimes that are difficult to elucidate, especially those committed against the tax system, the financial system and the public administration, the so-called white-collar crimes, which brings undeniable effectiveness to Administrative Law and Criminal Law. Although it is not a new institute in the Brazilian legal system, based on the fact that other Brazilian laws have already provided for the possibility of entering into agreements as a way of applying consensual justice in the criminal and administrative scope, the AntiCorruption Law has some gaps that need to be elucidated. For example, throughout its provisions, the Anti-Corruption Law is silent about the criminal treatment that will be given to individuals linked to companies that are signatories of leniency agreements, leaving them in a situation of doubt and uncertainty, which, in practice, brings legal uncertainty and prevents the institute from being applied efficiently and harmoniously. The present master thesis intends, therefore, to list and analyze not only the possibilities of granting criminal benefits to individuals within the scope of leniency agreements, through the study of the current legislation, including the other areas of law that addresses the subject, such as the Civil and Administrative Law, but also, and mainly, to analyze the criminal treatment that will be given to the agents of legal entities that may enter into a leniency agreement based on Law 12.846/13.